2018
DOI: 10.1155/2018/9843416
|View full text |Cite
|
Sign up to set email alerts
|

Energy Evolution Behavior and Mesodamage Mechanism of Crumb Rubber Concrete

Abstract: The energy evolution behaviour and mesodamage mechanism of CRC (crumb rubber concrete) were investigated by laboratory experiments and numerical simulations. The mesoscopic physical and mechanical parameters of CRC (crumb rubber concrete) materials were analyzed and determined by the discrete element method and trial-and-error method, and the mechanism and evolution of microcracks propagation during CRC failure were studied based on the parallel-bond model. The relationship among dissipation energy, damage thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Yu and Zhu [2] found that the consistency and initial density of cement mortar decreased as the rubber particle size increased and the porosity of the mortar increased as the rubber particle size decreased. Di et al [15] found a strong correlation between the damage threshold of CRC (crumb rubber concrete) and the amount of energy that was dissipated at the peak strength, where a CRC containing 25% rubber by mass exhibited the largest damage threshold in laboratory experiments and numerical simulations. Li and Xu [16] studied the effect of adding basalt fibers on the dynamic mechanical properties of concrete under impact loading.…”
Section: Introductionmentioning
confidence: 99%
“…Yu and Zhu [2] found that the consistency and initial density of cement mortar decreased as the rubber particle size increased and the porosity of the mortar increased as the rubber particle size decreased. Di et al [15] found a strong correlation between the damage threshold of CRC (crumb rubber concrete) and the amount of energy that was dissipated at the peak strength, where a CRC containing 25% rubber by mass exhibited the largest damage threshold in laboratory experiments and numerical simulations. Li and Xu [16] studied the effect of adding basalt fibers on the dynamic mechanical properties of concrete under impact loading.…”
Section: Introductionmentioning
confidence: 99%
“…e reason for this is that the rubber powder weakens the shear surface of the concrete, resulting in a reduction in concrete shear stress. Di et al [6] used uniaxial compression tests on cylinders to calculate the elastic strain energy release ratio of rubber powder concrete to characterize the toughness of rubber powder concrete. He found that the incorporation of rubber powder reduced the brittleness of the concrete and improved its toughness.…”
Section: Introductionmentioning
confidence: 99%